ALTERNATIVE THEORIES OF CAPITAL STRUCTURE - Xhaferi, Seadin; Xhaferi, Besa (European Scientific Journal, ESJ, 2015)
The beginning of the study of financing mix is after the Modigliani and Miller theorem and its unrealistic assumptions under which the source of finance does not impact the capital structure of the firm. Continuously after the M-M theorem new theories are developed. In this paper we are going to look at these alternative theories for sources of financing with a specific detail on the: Trade off theory and Pecking order theory. We provide evidence how this theories cope in practice of business.